Comparative analysis of macroalgae supplementation on the rumen microbial community: Asparagopsis taxiformis inhibits major ruminal methanogenic, fibrolytic, and volatile fatty acid-producing microbes in vitro - O’Hara, Eóin; Terry, Stephanie A.; Moote, Paul; Beauchemin, Karen A.; McAllister, Tim A.; Abbott, D. Wade; Gruninger, Robert J. (Frontiers in Microbiology, 2023)
Seaweeds have received a great deal of attention recently for their potential as methane-suppressing feed additives in ruminants. To date, Asparagopsis taxiformis has proven a potent enteric methane inhibitor, but it is a priority to identify local seaweed varieties that may hold similar properties. It is essential that any methane inhibitor does not compromise the function of the rumen microbiome. In this study, we conducted an in vitro experiment using the RUSITEC system to evaluate the impact of A. taxiformis, Palmaria mollis, and Mazzaella japonica on rumen prokaryotic communities. 16S rRNA sequencing showed that A. taxiformis had a profound effect on the microbiome, particularly on methanogens. Weighted Unifrac distances showed significant separation of A. taxiformis samples from the control and other seaweeds (P<0.05). Neither P. mollis nor M. japonica had a substantial effect on the microbiome (P>0.05). A. taxiformis reduced the abundance of all major archaeal species (P<0.05), leading to an almost total disappearance of the methanogens. Prominent fibre-degrading and volatile fatty acid (VFA)-producing bacteria including Fibrobacter and Ruminococcus were also inhibited by A. taxiformis (P<0.05), as were other genera involved in propionate production. However, the abundances of several other major ruminal bacteria (e.g., Prevotella) were increased by A. taxiformis, suggesting the rumen microbiome adapted to an initial perturbation. Our study provides baseline knowledge of microbial dynamics in response to seaweed feeding over an extended period and suggests that feeding A. taxiformis to cattle to reduce methane may directly or indirectly inhibit important fibre-degrading and VFA-producing bacteria.